Defined by wine : a study of sacramentalism in George HerbertÊ¾s poetry - Goddard, Kevin Graham (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1988)
This dissertation proposes that George HerbertÊ¾s poetry may profitably be understood as a sacramental means by which the divine is made present in temporal existence. In order to support this claim, the relation between sacramental symbolism and literary symbolism, particularly HerbertÊ¾s, is examined from a number of perspectives. The symbolic meanings suggested by HerbertÊ¾s title (The Temple), and their relation to sacramentalism are considered in the opening chapter. This includes a consideration of some of the background to the analogical thinking prevalent in both the seventeenth-century and Herbert. It is followed in the second chapter by an examination of some of the modern theories about how literary symbolism may relate to sacramental symbolism, a discussion which is followed by a consideration of this dissertation's argument in relation to modern scholarship. The chapter ends with a reading of ÊºThe FlowerÊº. The third chapter discusses the poet's attempt to imitate the divine by ÊºcopyingÊº both Scripture and Nature, and this includes a consideration of the allegorical and hieroglyphic modes of thought prevalent in the poems. The concern with imitation encourages an examination of the poet's frequent invitation for God actually to assume the poet's role, and this is the subject of the fourth chapter. The argument suggests that the poet's attempt to ÊºsacrificeÊº his own writing may be seen in his concern with corporate imagery and corporate (impersonal) structures. The five ÊºAfflictionÊº poems are examined as examples of the first, while structures such as synecdoche and metonymy are examined as examples of the second. The final chapter considers aspects of narrative time in the poems, particularly the sense often evoked of the eternal being imminent in the present. This involves a consideration of both liturgical imagery, and what may be called liturgical structures as they can be seen to operate in the poems. Particular examples of the latter are the relation between the liturgical anamnesis and the poems, as well as certain narrative structures that may be called ÊºachronisticÊº.
Keywords: Herbert, George, 1593-1633 -- Criticism and interpretation; Christian poetry, English -- History and criticism